2013
DOI: 10.4274/jcrpe.1127
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Insulin Resistance by HOMA-IR and its Cut-off Value to Identify Metabolic Syndrome in Urban Indian Adolescents

Abstract: Objective: Insulin resistance (IR) and associated metabolic abnormalities are increasingly being reported in the adolescent population. Cut-off value of homeostasis model of assessment IR (HOMA-IR) as an indicator of metabolic syndrome (MS) in adolescents has not been established. This study aimed to investigate IR by HOMA-IR in urban Indian adolescents and to establish cut-off values of HOMA-IR for defining MS.Methods: A total of 691 apparently healthy adolescents (295 with normal body mass index (BMI), 205 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
81
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(98 citation statements)
references
References 40 publications
11
81
0
Order By: Relevance
“…Six studies,18 , 20 - 23 were carried out in foreign countries between 2005 and 2015 and one19 was performed with Brazilian adolescents in 2011. The smallest sample consisted of 57 participants23 and the largest had 3203 22.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six studies,18 , 20 - 23 were carried out in foreign countries between 2005 and 2015 and one19 was performed with Brazilian adolescents in 2011. The smallest sample consisted of 57 participants23 and the largest had 3203 22.…”
Section: Resultsmentioning
confidence: 99%
“…Six studies17 , 18 , 20 , 23 preferred the use of the cutoff point with high sensitivity and specificity and one study19 prioritized the cutoff with greater sensitivity. The lower cutoff points found were 1.65 for girls and 1.95 for boys19 and the highest were 3.82 for girls and 5.22 for boys 18…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their study on adolescents found 34.5% insulin resistance with mean HOMA-IR increasing with sexual maturity and obesity. [9] John et al reported 14.4% insulin resistance in their study on students of a medical college in South India, [12] but they chose to measure insulin resistance by triglycerides to HDL-cholesterol ratio instead of by HOMA-IR.…”
Section: Discussionmentioning
confidence: 99%
“…[8] HOMA-IR > 2.5 has been reported to identify a large number of adolescents as having metabolic syndrome in different categories of Body Mass Index (BMI). [9] High prevalence of insulin resistance in the general school and college population has been reported. [10] However, studies on medical students is mostly restricted to obesity.…”
Section: Access This Article Online Quick Response Codementioning
confidence: 99%